(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Indian civilisation is one of the oldest in the world. It has had a rich philosophical past that isnow being brought out of obscurity. Environment and ecological concerns are important considerations inthe modern period. A study of India‘s ancient and medieval literature shows that these were topics ofconcern even during those times. Indian philosophers and thinkers had provided numerous nuggets ofwisdom pertaining to the need for care and respect of environment, plants and animals. This articleexamines the environment oriented thinking in Indian philosophy in context of economics andmanagement of resources. The sources of information used are secondary sources such as books andarticles published in various journals